Medication compliance and its associates among rural elderly with non-communicable chronic diseases in Shandong province - Zhao-rong GAO; Wen-zhe QIN; Jiao ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the prevalence and influencing factors of medication compliance among elderly non-communicable chronic diseases (NCDs) patients in rural Shandong province and to provide a reference for effectively improving medication compliance of the patients.MethodsUsing stratified multistage random cluster sampling, we conducted a questionnaire survey among 7 088 rural residents aged 60 years and above in three prefectures of Shandong province during August - September, 2017. Then, the residents diagnosed with NCDs (including hypertension, diabetes, cardiovascular diseases, and tumor) were identified and their medication compliance and its influencing factors were analyzed.ResultsAmong 7 070 participants with complete information, 3 456 were NCDs patients; of the patients, 37.6% (1 229) were assessed being compliant to their medication. The results of unconditional multivariate logistic regression analysis revealed that the patients aged ≥ 70 years, not being employed, having a poor self-rated health condition, suffering from two NCDs, and with a moderate or high self-efficacy score were more likely to have medication compliance; whereas, the patients with the education of junior high school and below, without regular daily diet, without hospitalization during past one year, and with a fair or poor mental health situation were less likely to have medication compliance.ConclusionThe medication compliance is poor and influenced by multiple factors including age, education, employment, daily diet regularity, self-rated health, disease comorbidity, hospitalization during previous one year, mental health, and self-efficacy among rural elderly residents with non-communicable chronic diseases in Shandong province.